CTAB Influence on the Hydrolytic Stripping of Nickel Ferrite - Jiménez Muñiz Adrián; Verdejo Palacios Alejandra; Palacios Beas Elia Guadalupe (Materials Research)
The role of the CTAB concentration (0.0 M, NS; 5x10-4 M, ½CMC; 2x10-3 M, 2CMC) and the residence time on the composition, morphology and magnetic properties for the nickel nanoferrite formation by hydrolytic stripping (33% v/v naphthenic/kerosene) at 200°C were studied. X-ray, SEM/EDS, FTIR, VSM, and ICP/OES were used to characterise solids and solutions. Regardless of the experimental conditions, all samples present nickel spinel ferrite as the only phase, with similar Fe/Ni molar ratio. However, those precipitates in the presence of CTAB show more homogeneous morphology than in its absence. CTAB at high concentration (2CMC) increases the discharge rate, reaching 100% at 40 min; 14.79 nm average size nanoparticles were obtained, with better magnetic properties (Ms=53.02 emu/g and Hc=35.59 Oe) than those achieved at low concentration (½CMC) and in the absence of CTAB.